Trends in the BS Clothing Technology program theses from 2016 to 2022 - Ferrer, Cristina Maria M.; Lumawig, Maria Josephine T. (Quezon City University of the Philippines Diliman, 2025)
Research is essential to education. It is the methodical process of discovering answers to questions brought about by an observed phenomenon. The BS Clothing Technology (BSCT) program, offered by the University of the Philippines, aims to make research-based contributions to society. This study, based on Abenojar’s 2016 thesis, employed a mixed-methods approach to analyze the trends presentamong the undergraduate theses produced by BSCT students from 2016 to 2022. Through content analysis and descriptive statistics, the study identified the factors that led students to choose their research topic, categorized the theses based on the four thrusts of specialization of the BSCT curriculum, the Department’s research agenda, and the beneficiaries of the research. Purposive sampling was employed to select the range of studies to be analyzed as well as to select the 30 respondents for the survey. The findings indicated the same findings of Abenojar, that personal inclination or interest and desire to innovate, create, or develop are the prevailing factors for the choice of thesis topics. However, a value-driven factor, need of family or friend, which ranked high based on Abenojar’s findings, was among the low-ranking factors. According to the four thrusts of the BSCT program, the trend seems to remain the same compared to Abenojar’s 2016 study, where design is the leading thrust among the theses. Based on the research agenda, similar findings to Abenojar’s study emerged, where culture was most popular and policies was the least popular theme. Finally, most studies point to the category others, which includes concerned individuals and groups, as the beneficiary, as opposed to Abenojar’s study, which identified producers as the top beneficiary. It is recommended that the BSCT program further foster a clear appreciation and actual practice of the values of the College of Home Economics “to enhance the quality of day-to-day living of families and consumers”. Broader and more intensive studies are recommended, ideally with a wider scope of theses and to more aspects, such as the methodology. Proper classification of the different categories, such as that of the beneficiaries, is also recommended.
In partial fulfillment for the Degree of Bachelor of Science in Clothing Technology
Thesis
Keywords: Clothing and dress -- Research; College students -- Research; Dissertations, Academic -- Philippines; Clothing technology; Research trends; Research motivation